The relevancy and admissibility of evidence obtained through unlawful means: a comparative legal appraisal - Mohamad Yunus, Mohamad Ismail (Institut Kefahaman Islam Malaysia (IKIM), 2004)
The rules relating to the admissibility or inadmissibility of illegally or improperly obtained evidence is a matter of court's discretion. The question of whether this kind of evidence ought to be rejected because it was obtained illegally, that is, by a crime, a tort or a breach of official police regulations, involves a difficult choice between two competing policies. In support of the admissibility of such evidence it is argued that since its reliability is normally not affected by the manner in which it was obtained, it ought not to be rejected since the consequence would often be that a guilty person would be acquitted. On the other hand, it is argued that to admit such evidence involves the tacit encouragement of improper police practices, and that such practices constitute at least as great an evil as the occasional acquittal of a guilty accused. This paper therefore aims at identifying the position and recent development on the law of illegally obtained evidence. This research emphasizes on the comparative studies between different countries, namely Malaysia, United Kingdom, Australia, New Zealand and the United States of America. The position in Islamic perspective is also well considered.